2018
DOI: 10.1038/s41598-018-33255-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualising peripheral arterioles and venules through high-resolution and large-area photoacoustic imaging

Abstract: Photoacoustic (PA) imaging (PAI) has been shown to be a promising tool for non-invasive blood vessel imaging. A PAI system comprising a hemispherical detector array (HDA) has been reported previously as a method providing high morphological reproducibility. However, further improvements in diagnostic capability will require improving the image quality of PAI and fusing functional and morphological imaging. Our newly developed PAI system prototype not only enhances the PA image resolution but also acquires ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…In the subsequent generations, to increase the field of view, the rotational scanning is replaced by a rectilinear scan of the whole array in a spiral pattern. [45][46][47] In addition, the number of the array elements is increased to 512, and the central frequency is reduced to 2 MHz. The spiral scan is such that PA data acquired is at equidistant locations.…”
Section: Hemispherical Imaging Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subsequent generations, to increase the field of view, the rotational scanning is replaced by a rectilinear scan of the whole array in a spiral pattern. [45][46][47] In addition, the number of the array elements is increased to 512, and the central frequency is reduced to 2 MHz. The spiral scan is such that PA data acquired is at equidistant locations.…”
Section: Hemispherical Imaging Systemsmentioning
confidence: 99%
“…So far, US imaging could only be achieved using a secondary transducer array, which needs additional image co-registration. 47 Another hemispherical system implemented by Oraevsky et al 51 features an arc-shaped transducer that is rotated around the breast. This system, called the laser optoacoustic imaging system assembly (LOUISA-3D), consists of two subsystems-the PA subsystem and the US subsystem.…”
Section: Hemispherical Imaging Systemsmentioning
confidence: 99%
“…We contribute to the field of photoacoustic breast imaging with our PAM 2 system, which is different from other systems recently presented [15][16][17] in terms of illumination and detector specifications. We show that adding more illumination beams and changing the ratio of delivered energy to these beams alters the observed results.…”
Section: Introductionmentioning
confidence: 99%
“…Several other research groups are working in the field of photoacoustic tomographic breast imaging. Matsumoto et al 15 showed a (breast) imaging system (PAI-04) where a woman is prone on a bed with one breast inside a breast-holding cup. A hemispherical-shaped detector array (center frequency 4 MHz) is used to measure the ultrasound as the breast is illuminated by a large beam, directed at the ventral side of the breast.…”
Section: Introductionmentioning
confidence: 99%
“…It can afford high resolution images in deep tissue based on optical absorption. PAT has shown its ability in breast cancer , thyroid cancer , vascular examination , inflammatory arthritis and osteoarthritis , oral cancer , bone pathology and dermatology in human studies. PAT of vasculature can be achieved because hemoglobin is concentrated in blood vessels with strong optical absorption.…”
Section: Introductionmentioning
confidence: 99%